Assessing the impact of faculty development workshops: a change initiative in medical education in Pakistan - Zehra, Tabassum; Sana Saeed; Malik, Marib Ghulam Rasool; Ali, Rahila; Sultan, Amber; Tariq, Muhammed (Journal of the Pakistan Medical Association, 2025)
Faculty development is pivotal to enhancing pedagogical skills among health professionals. The current cross-sectional study was planned to evaluate satisfaction as well as short-term and long-term impacts of faculty development workshops on academic practices through a continuous faculty development programme. Data was collected through post-workshop evaluations, and follow-up questionnaires. Over four years, 28 workshops engaged 164 participants. High satisfaction was reported, with 65(76.5%) to 76(89.4%) strongly agreeing on factors, like gaining new knowledge, clarity, relevance and participation. Most respondents of the follow-up questionnaire reported fair to great eagerness for further learning 44(91.7%). Perceived challenges included preoccupation with work commitments 30(62.5%) and lack of institutional support 18(39.6%). Positive correlations highlighted the link between workshop satisfaction and self-reported change. Key Words: Health professional education, Medical education, Medical educators, Teachers.